Former students' perspectives on moral education learning - Yasin, Maizura; Arshad, Mohd Mursyid; Mohamed Mokhtar, Marzni; De Asildo, Noor Zulina S. (South East Asian Association for Institutional Research, 2024)
This study explores the learning experiences of former Moral Education (ME) students in one of Sabah’s districts on the East Coast. Since the introduction of ME subjects is tailored to the students’ diverse religious backgrounds and beliefs, the student’s background in the Sabah East Coast district, where the majority are Christians, might portray an alternate narrative of the aspects of the ME learning experience among the students. This study employed the qualitative research design with a phenomenological approach to understand the experiences of former ME students in learning the subject at school. Data were gathered through semistructured interviews and supplemented written documents, which were then analyzed using thematic analysis, revealing three main themes, which are: (i) Relating values to situations; (ii) Memorizing; and (iii) Conforming to syllabus and policy. They have influenced the success or failure of ME’s goal, which is to produce virtuous human beings rather than academic achievement. Implications were discussed, emphasizing the role of educators and policymakers in ensuring that ME teachers understand the fundamental goal of the subject to allow for its implementation to be successful in nurturing virtuous human beings as desired continuously until higher education level.